ANALISIS RESEPSI ANAK MUDA KOTA DENPASAR TERHADAP KRITIK SOSIAL PADA IKLAN SAMPOERNA A MILD “SOLUSI LO MASALAH BUAT GUE” VERSI LAMPU MERAH - Syahla Afifah, Baiq Tina; Gelgel, Ni Made Ras Amanda; Suryawati, I Gusti Agung Alit (E-Jurnal Medium, 2024)
Cigarette product advertisements are not allowed display their products directly because they have their own broadcast regulations, advertisers are required to be more creative in making their advertisements so as not to violate regulations but can still market their products and maintain their product's brand image. Sampoerna A Mild advertisement is one of the creative cigarette advertisements that raises social criticism as its advertising theme, in contrast to other cigarette advertising themes that commonly display masculinity or lifestyle as a theme. This study uses a qualitative approach with descriptive methods and uses reception theory of the encoding-decoding with the analysis of Stuart Hall. This study aims to determine the reception that occurs of youth people in Denpasar City towards social criticism in the advertisement of Sampoerna A Mild. The results of this research analysis show that four people in the Dominant Position and two people in the Negotiated Position.